Gawad Plaridel lecture 2017 - Monzon Palma, Ma. Christina; Rimban, Luz (2018)
Access online through this link: https://www.plarideljournal.org/article/4433
Keywords: UP Gawad Plaridel; Speeches, addresses, etc; Broadcast journalism